El talento psicomotor y las mujeres en el deporte de alta competición - Alfaro, Élida (FAISCA: Journal of High Abilities, 2002)
Nowadays, nobody has got doubts about the importance of taking care of every area in which anyone is able to manifest himself when our aim is managing to reach the full development of human being, as well cognitive, affective, social as psychomotor areas. Although this, excluding the pure sporting field, there are still some obstacles when we try to include in the selected group of the Gifted Ones the people that has got high motor capacities. The study of the persons that present, from early ages, predisposition to resolve motivity problems through the carrying out of motivity highly efficient behaviors has taken to the identification of the factors cognitive, physical and functional that support sporting talent and have allowed to establish models of intervention for the most capable ones to reach personal and social success. The high competition sport sets up the highest levels of sporting realization due to its objectives, and the development are based on the obtaining of the best results, which ones are valuated through the competence between subjects that are looking for the same aims and in contexts specifically designed for this purpose. Because all of this, here there are also the most adequate setting for the demonstration and valuation of the sporting talent. The high contest sport; and, inside this one, the Olympic Games represent the highest exponent of the achievements obtained by sport talented subjects. In the sports high competition ambit, in general, and in the Olympic Games, in particular, the women with sport talent have fighted and keep on fighting to obtain the proper support and social and sporting recognition. Biographies of some of the most remarkable sportswomen discover to us, close to their sport success, the discrimination they had stood for ages, as well as all the effort, the giving ups and also some other personal and social successes they have been capable to combine with sport and that have been exposure of their excellence.